(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study examines the importance of teaching supervision in improving teacher competency and learning quality at SMK PGRI 6 Ngawi. This supervision is a strategic key to producing competitive graduates in the workforce, as the quality of graduates is highly dependent on effective teacher teaching. The method used in this study was a qualitative approach with a case study. The research subjects were purposively selected, consisting of the Principal, the Vice Principal for Curriculum, and six teachers. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed descriptively qualitatively. The validity of the findings was strengthened by data triangulation. The results showed that SMK PGRI 6 Ngawi implemented a combined clinical and collaborative supervision model. This model has proven successful in improving teachers’ pedagogical skills, encouraging learning innovations such as project-based learning, and fostering teachers’ awareness of self-reflection. Specifically, this supervision model, which focuses on two-way dialogue and continuous development, significantly improved teacher professionalism. Despite facing challenges such as limited time and resources, its successful implementation was supported by the strong commitment of the school leadership and the enthusiasm of the teachers. In conclusion, learning supervision at SMK PGRI 6 Ngawi is an important instrument for improving the quality of education. If desired, it is recommended that schools develop peer supervision programs and utilize digital technology to overcome time constraints, so that the supervision process becomes more systematic and adaptive.